The silicon isotope composition of granites - Savage, P; Georg, R; Williams, H; Turner, S; Halliday, A; Chappell, B (2012)
Because weathering results in preferential incorporation of the lighter Si isotopes into clay minerals, the Si in magmas derived from (meta)sedimentary lithologies enriched in such phases should also be isotopically light, relative to melts derived from igneous sources. With the advent of new high precision techniques it should therefore be possible to resolve such differences. Hence, Si isotopes have to potential to distinguish between, and characterise, different magmatic source regions.To explore this, here we report the Si isotopic compositions of a suite of Phanerozoic I-, S- and A-type granites and mineral separates, as well as samples of associated country rock. The whole-rock data fall between δ 30Si=-0.40 and -0.11±0.04‰ (95%s.e.). This range is more limited than that defined by previous low precision measurements of granites, but is significantly broader than that displayed by more recent, high precision, measurements of high-Si extrusive igneous rocks. As predicted, S-type granites are, on average, isotopically lighter than I- and A-type samples, and negative correlations with alumina saturation index (ASI) values and initial 87Sr/ 86Sr provide evidence that Si isotope variations in granites can be explained by variable incorporation of an enriched sedimentary component. However, the relatively small isotopic perturbations and apparent degree of overlap between granite affinities suggest that Si isotopes are not as sensitive to sedimentary input, relative to more established proxies such as, for example, O isotopes. The average Si isotope value of all granites analysed in this study is δ 30Si=-0.23±0.15‰ (2s.d.), which is entirely consistent with a recently published estimate for the continental crust, based on an andesitic bulk composition and the well defined relationship between Si isotopes and magmatic fractionation. © 2012 Elsevier Ltd.